الاحتجاج بالحديث النبوي عند علماء اللغة المتقدمين - تأصيل للإشكال النحوي وقراءة في الواقع اللغوي والبلاغي - بوخزنة, حمزة (جامعة الوادي - University of Eloued, 2019)
نسعى من خلال هذه الدراسة الكشفَ عن واقع الحديث النّبوي في جملة لا بأس بها من الدراسات اللغوية، لندفع كل ما قد يعلق به من شبهات واهية تزعزع ثقة الباحثين بأصالته وقيمته اللغوية، وهذا من خلال تقديم قراءة دقيقة لأصل الإشكال النحوي من خلال المعايير التي ارتضاها العلماء المتقدمون في تأسيس علوم اللغة بادئ الأمر، ومن المعايير الحاسمة التي وقفنا عليها عندهم السّماع أو النقل كما يطلق عليه ابن الأنباري، وهو رأس الأمر في اثبات عربيّة اللفظ الذي يقتضي صحّة الاحتجاج على تقعيد اللغة . ثم سنتكلم عن ضوابط الاحتجاج، وسنشفع ذلك ببيان مفصل للواقع الاحتجاجي بالحديث من خلال تتبع مظاهره في التراث اللغوي والبلاغي . Through this study, we seek to uncover the reality of the Prophet's Hadith in a good number of linguistic studies, to push all the flimsy suspicions that may be attached to it that undermine researchers confidence in its originality and linguistic value, and this by providing an accurate reading of the origin of the grammatical problem through the standards that scholars have accepted. Those advanced in establishing linguistic sciences in the beginning, and one of the critical criteria upon which we stood by them is listening (Al-Samae) or transmitting (Al-Naqel(, as Ibn Al-Anbari calls it, and it is the head of the matter in proving the Arabic pronunciation that requires the validity of the protest against the complexity of the language. Then we will talk about the controls of protest, with a detailed explanation of the reality of the protest in the hadith by tracing its manifestations in the linguistic and rhetorical heritage.
مقال
Keywords: الحديث النبوي؛ الاحتجاج؛ الضوابط؛ النحو؛ البلاغة؛ اللغة; Prophet's Hadith; Protest; Controls; Grammar; Rhetoric,The language